Možnosti uveljavljanja okoljskih zahtevkov pred mednarodnimi pogodbenimi telesi mednarodnih pogodb o človekovih pravicah - Sancin, Vasilka (Podjetje in delo, 2020)
The article tackles the developing jurisprudence of national courts and international human rights treaty-based bodies, where plaintiffs argue violations of their human rights due to environmental changes, in particular in light of climate change. It is noticeable that national courts increasingly recognise legal standing to individuals for bringing their claims, while there is also an emerging trend of recognising positive obligations of states for ensuring human rights, which demand from them active engagement in environmental problems, including climate change. When plaintiffs fail to succeed before domestic courts, and the state is a party to treaties recognising a possibility of bringing individual communications to committees as monitoring bodies established on the basis of such treaties, the individuals increasingly, in spite of the length of procedures, decide to initiate international proceedings against the state. The article also illuminates the pertinent practice of the Human Rights Committee.
Keywords: climate change; Human Rights Committee; human rights treaty-based bodies; International Covenant on Civil and Political Rights; international human rights law; Mednarodni pakt o državljanskih in političnih pravicah; mednarodno pravo; mednarodno pravo človekovih pravic; Odbor ZN za človekove pravice; podnebne spremembe; pogodbena telesa mednarodnih pogodb o človekovih pravicah; Teitiota